Analisis Kualitas Bahan, Desain Bangunan Dan Kepuasan Pelanggan Pada CV. Tiga Bunga - Palma Juanta; Amorita Sarozato Zendrato; Andra Hendarto; Hanisa Laili Zahra; Pierre Abrian Naibaho; Rizky Duentha Sitepu; Ananda Sry Aulia Rizky (Lembaga Pengembangan Kinerja Dosen, 2024)
Customer satisfaction is a crucial factor in maintaining and enhancing competitiveness in the construction industry. This study aims to explore the influence of material quality and building design on customer satisfaction at CV Tiga Bunga. A quantitative method was employed, collecting data through questionnaires from 50 customers who have used CV Tiga Bunga's services. Data were analyzed using descriptive analysis, pearson correlation, and multiple linear regression. The results indicate that material quality (MQ) and building design (BD) have a significant positive correlation with customer satisfaction (CS). Regression analysis shows that both material quality and building design jointly significantly influence customer satisfaction, with building design exerting a stronger impact. These findings contribute significantly to practitioners and managers at CV Tiga Bunga in enhancing quality management and design strategies to improve customer satisfaction.